Hacking World of Warcraft - Gilbert, D; Whitehead, J (John Wiley and Sons, 2007)
World of Warcraft is your world. You are fearless. You are in cmomand. And when you can command these awesome addons, macros, and customizations, you'll savor the heady brew of victory. From the masters who gave us Atlas and PerfectRaid/Clique, you'll learn how to gain an advantage in combat, write spell-casting macros, work with frames and XML, develop Lua scripts that work with the WoW API, and more. Yeah they're legal. But don't let that hold you back.